An excess of dusty starbursts related to the Spiderweb galaxy - Dannerbauer, H.; Kurk, J.D.; De Breuck, C.; Wylezalek, D.; Santos, J.S.; Koyama, Y.; Seymour, N.; Tanaka, M.; Hatch, N.; Altieri, B.; Coia, D.; Galametz, A.; et al. (EDP Sciences, 2014)
We present APEX LABOCA 870 μm observations of the field around the high-redshift radio galaxy MRC1138−262 at z = 2.16. We detect 16 submillimeter galaxies (SMGs) in this ~140 arcmin2 bolometer map with flux densities in the range 3–11 mJy. The raw number counts indicate a density of SMGs that is up to four times that of blank field surveys. Based on an exquisite multiwavelength database, including VLA 1.4 GHz radio and infrared observations, we investigate whether these sources are members of the protocluster structure at z ≈ 2.2. Using Herschel PACS and SPIRE and Spitzer MIPS photometry, we derive reliable far-infrared (FIR) photometric redshifts for all sources. Follow-up VLT ISAAC and SINFONI NIR spectra confirm that four of these SMGs have redshifts of z ≈ 2.2. We also present evidence that another SMG in this field, detected earlier at 850 μm, has a counterpart that exhibits Hα and CO(1–0) emission at z = 2.15. Including the radio galaxy and two SMGs with FIR photometric redshifts at z = 2.2, we conclude that at least eight submm sources are part of the protocluster at z = 2.16 associated with the radio galaxy MRC1138−262. We measure a star formation rate density SFRD ~1500 M⊙ yr-1 Mpc-3, four magnitudes higher than the global SFRD of blank fields at this redshift. Strikingly, these eight sources are concentrated within a region of 2 Mpc (the typical size of clusters in the local universe) and are distributed within the filaments traced by the HAEs at z ≈ 2.2. This concentration of massive, dusty starbursts is not centered on the submillimeter-bright radio galaxy which could support the infalling of these sources into the cluster center. Approximately half (6/11) of the SMGs that are covered by the Hα imaging data are associated with HAEs, demonstrating the potential of tracing SMG counterparts with this population. To summarize, our results demonstrate that submillimeter observations may enable us to study (proto)clusters of massive, dusty starbursts.